2021
DOI: 10.1017/s1368980021002330
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and nutrient intake among participants of a Brazilian health promotion programme: a cross-sectional study

Abstract: Objective: Developing health promotion activities, aimed at healthy food intake, is essential for improving quality of life and reducing the prevalence of chronic diseases. Thus, the objective of this study is to describe both dietary and nutrient intake, according to length of participation in a health-promotion service (Programa Academia da Saúde - PAS). Design: A cross-sectional study was carried out with a representative sample of PAS units in vulnerable areas of the city. Dietary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…5, of September 28, 2017, nutrition is a component of the axis of actions (promotion of healthy eating) that guides the activities to be developed in the "Academia da Saúde" poles. The relevance of nutrition in the context of the "Academia da Saúde" Program is explained by the numerous themes related to the topic investigated by the studies, which focused on the consumption of fruits and vegetables (17,26,28,29), dietary profile (27,41), access to healthy food consumption (22, 23, 25, 30-33, 53, 54), nutritional knowledge (20,21,24), identification of barriers and facilitators for the intake of fruits and vegetables (18, 19, 40), and interventions aimed at promoting the intake of healthy foods (44-46). The relevance of investigating this topic by the included studies is even more understandable when considering that dietary intake has a direct relationship with the occurrence of NCDs (e.g., cancer, heart disease, and obesity) (91)(92)(93), as prevention and control of morbidities and risk factors associated with NCDs are the pillars of the creation of the "Academia da Saúde" Program (8).…”
Section: Discussionmentioning
confidence: 99%
“…5, of September 28, 2017, nutrition is a component of the axis of actions (promotion of healthy eating) that guides the activities to be developed in the "Academia da Saúde" poles. The relevance of nutrition in the context of the "Academia da Saúde" Program is explained by the numerous themes related to the topic investigated by the studies, which focused on the consumption of fruits and vegetables (17,26,28,29), dietary profile (27,41), access to healthy food consumption (22, 23, 25, 30-33, 53, 54), nutritional knowledge (20,21,24), identification of barriers and facilitators for the intake of fruits and vegetables (18, 19, 40), and interventions aimed at promoting the intake of healthy foods (44-46). The relevance of investigating this topic by the included studies is even more understandable when considering that dietary intake has a direct relationship with the occurrence of NCDs (e.g., cancer, heart disease, and obesity) (91)(92)(93), as prevention and control of morbidities and risk factors associated with NCDs are the pillars of the creation of the "Academia da Saúde" Program (8).…”
Section: Discussionmentioning
confidence: 99%
“…Actions developed in the health promotion services are strategic to promote adequate and healthy food choices. For example, longer participation in the PAS seems to be effective in improving the profile of food and nutrient consumption of its clients, as evidenced by a cross-sectional study that identified an increase in the consumption of home-prepared food and a reduction in UPF, as well as lower energy and fat consumption, and higher levels of carbohydrates, vitamin C, and calcium among those with longer time as participation in the health service [ 24 ]. A previous longitudinal study showed a reduction in the consumption of UPF and an increase in home-prepared food [ 23 ], possibly corroborating the results of this study, which showed an improvement in the consumption of nutrients over time, including those related to the prevention and control of NCDs, following the recommendations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The homemade measures of the food and reported recipes were transformed into grams or milliliters using tables and manuals to assess food consumption [ 20 , 21 , 22 ], and food labels and measurements performed by the research team (weighing and standardization) [ 23 , 24 ]. Then, the R24h data were tabulated in a specific program, used in a national food survey, by a trained and supervised team [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations